2009
DOI: 10.1007/s00436-009-1654-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a novel serpin gene of Clonorchis sinensis, highly expressed in the stage of metacercaria

Abstract: The serpins are a superfamily of proteins (350-500 amino acids in size) that fold into a conserved structure. From about 3,475 unigenes of Clonorchis sinensis metacercaria, a novel gene-encoding serpin was identified and characterized. The opening reading frame is 1,149 bp encoding 382 amino acids. The deduced amino acid sequence shows high identity to previously reported serpins from C. sinensis and other helminthic parasites. A typical serpin signature was found by motif search. The recombinant C. sinensis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The construction of C. sinensis metacercaria cDNA library was described previously (Yang et al 2009). About 3,475 unigenes were obtained, in which a complete sequence coding C. sinensis metacercaria glycerol 3-phosphate dehydrogenase (GPD) was recognized by BLASTx in NCBI (http://www.ncbi.nlm.nih.gov).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of C. sinensis metacercaria cDNA library was described previously (Yang et al 2009). About 3,475 unigenes were obtained, in which a complete sequence coding C. sinensis metacercaria glycerol 3-phosphate dehydrogenase (GPD) was recognized by BLASTx in NCBI (http://www.ncbi.nlm.nih.gov).…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant protein was eluted with 100 mM imidazole, and then imidazole was removed from protein by dialysis using phosphate-buffered to manufacturer's instructions and treated with DNase (Promega, USA), PCR was employed to amplify the transcripts of GPD (606 bp) and C. sinensis β-actin (GenBank accession No. EU109284, 323 bp), which was used as a positive control (Yang et al 2009;Yoo et al 2009). The sense and antisense primers for CsGPD were 5′-TATCGGGTCGGGAAACTGGG-3′, 5′-ACGGCA ACAATGTTCTTCAAAGC-3′, and for β-actin of C. sinensis were 5′-GGTGACGCTGAAGTATCCTATTG A-3′, 5′-CCAAAGCATAGCCCTCGTAGAT-3′, respectively.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Adult worms and infected livers of rabbits were stained by immunofluorescence techniques as described by Yang et al (10). Adult worms and infected liver were fixed with 10% neutral formalin and embedded with paraffin and then sliced into sections.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
“…6 In our previous study, one novel serpin named CsSERPIN was identified and characterized. 7,8 It is significantly highly expressed in metacercaria stage. The biochemical activities showed that rCsproSERPIN could significantly inhibit trypsin, chymotrypsin, and thrombin, indicating that it may play an important role in the information of metacercariae.…”
Section: Introductionmentioning
confidence: 99%